2018
DOI: 10.1002/cncr.31910
|View full text |Cite
|
Sign up to set email alerts
|

The impact of state parity laws on copayments for and adherence to oral endocrine therapy for breast cancer

Abstract: Background Adherence to endocrine therapy for breast cancer is often inadequate, in part because of out‐of‐pocket costs for medication. Numerous states have enacted parity laws to limit patient cost‐sharing for oral anticancer drugs. The objective of this study was to estimate the impact of these laws on patient copayments for and adherence to oral endocrine therapy for breast cancer. Methods Administrative health insurance claims data from 2007 to 2014 derived from a US health care database were used to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…In the current issue of Cancer, Chin and colleagues provide an evaluation of how parity has impacted out-of-pocket spending on endocrine therapy for the prevention of breast cancer recurrences, comparing states with and without oral oncology parity laws between 2007 and 2014. 1 Consistent with prior work, their study indicates that oral oncology parity laws did not consistently reduce out-of-pocket spending for endocrine therapy. 2 Indeed, parity reduced spending at the 25th percentile of spending for 2 drugs (anastrozole and exemestane), increased it for a third drug (letrozole), and had no effect on the fourth drug (tamoxifen).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In the current issue of Cancer, Chin and colleagues provide an evaluation of how parity has impacted out-of-pocket spending on endocrine therapy for the prevention of breast cancer recurrences, comparing states with and without oral oncology parity laws between 2007 and 2014. 1 Consistent with prior work, their study indicates that oral oncology parity laws did not consistently reduce out-of-pocket spending for endocrine therapy. 2 Indeed, parity reduced spending at the 25th percentile of spending for 2 drugs (anastrozole and exemestane), increased it for a third drug (letrozole), and had no effect on the fourth drug (tamoxifen).…”
supporting
confidence: 75%
“…In the current issue of Cancer , Chin and colleagues provide an evaluation of how parity has impacted out‐of‐pocket spending on endocrine therapy for the prevention of breast cancer recurrences, comparing states with and without oral oncology parity laws between 2007 and 2014 . Consistent with prior work, their study indicates that oral oncology parity laws did not consistently reduce out‐of‐pocket spending for endocrine therapy .…”
mentioning
confidence: 72%
“…The systematic review identified 3639 records, of which 105 full-text studies were retrieved [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ,…”
Section: Resultsmentioning
confidence: 99%
“…Additional efforts should be made to implement initiatives such as price transparency, insurance optimization, and financial navigation to mitigate the patient‐borne effects of cost sharing 45‐47 . Enactment of parity laws and efforts to limit ET out‐of‐pocket costs may also affect medication adherence 48 . Additional efforts such as coordination of transportation for clinic visits and use of telemedicine and personalized culturally tailored interventions may improve early discontinuation due to limited access to health care.…”
Section: Discussionmentioning
confidence: 99%